An electronic order set for acute myocardial infarction is associated with improved patient outcomes through better adherence to clinical practice guidelines. Issue 3 (3rd February 2014) - Ballesca, Manuel A.; LaGuardia, Juan Carlos; Lee, Philip C.; Hwang, Andrew M.; Park, David K.; Gardner, Marla N.; Turk, Benjamin J.; Kipnis, Patricia; Escobar, Gabriel J.
<x xml:space="preserve">Abstract</x> BACKGROUND Adherence to evidence‐based recommendations for acute myocardial infarction (AMI) remains unsatisfactory. OBJECTIVE Quantifying association between using an electronic AMI order set (AMI‐OS) and hospital processes and outcomes. DESIGN Retrospective cohort study. SETTING Twenty‐one community hospitals. PATIENTS A total of 5879 AMI patients were hospitalized between September 28, 2008 and December 31, 2010. MEASUREMENTS We ascertained whether patients were treated using the AMI‐OS or individual orders (a la carte). Dependent process variables were use of evidence‐based care; outcome variables were mortality and rehospitalization. RESULTS Use of individual and combined therapies improved outcomes (eg, 50% lower odds of 30‐day mortality for patients with ≥3 therapies). The 3531 patients treated using the AMI‐OS were more likely to receive evidence‐based therapies (eg, 50% received 5 different therapies vs 36% a la carte). These patients had lower 30‐day mortality (5.7% vs 8.5%) than the 2348 treated using a la carte orders. Although AMI‐OS patients' predicted mortality risk was lower (3.2%) than that of a la carte patients (4.8%), the association of improved processes and outcomes with the use of the AMI‐OS persisted after risk adjustment. For example, after inverse probability weighting, the relative risk for inpatient mortality in the AMI‐OS group was 0.67 (95% confidence interval: 0.52‐0.86). Inclusion of use of recommended therapies in risk adjustment eliminated the benefit of the AMI‐OS, highlighting its mediating effect on adherence to evidence‐based treatment. CONCLUSIONS Use of an electronic order set is associated with increased adherence to evidence‐based care and better AMI outcomes. Journal of Hospital Medicine 2014;9:155–161. © 2014 Society of Hospital Medicine